An Unusual Presence of Pulp Stones in a Pulp Chamber of the Permanent Maxillary Incisors - Sposito, Otávio Silva; Martos, Josué; Jacinto, Rogerio Castilho [UNESP] (Wolters Kluwer, 2021)
Anatomy of the root canal system determines the pathways of the endodontic treatment, which directly affect the success of the therapy. A pulp stone is often located in the pulp chamber and radiographically is viewed as radiopaque structures. This manuscript presents a case report of endodontic treatment performed in two permanent central maxillary incisors with pulp stones in a young female patient. Conclusively, the presence of pulp stones did not interfere in the quality of the endodontic procedures, and the outcome of the treatment was successful.
Keywords: Endodontics; pulp stones; root canal